2016
DOI: 10.1002/ecy.1450
|View full text |Cite
|
Sign up to set email alerts
|

Relatively stable response of fruiting stage to warming and cooling relative to other phenological events

Abstract: The timing of the fruit-set stage (i.e. start and end of fruit set) is crucial in a plant's life cycle, but its response to temperature change is still unclear. We investigated the timing of seven phenological events, including fruit-set dates during 3 years for six alpine plants transplanted to warmer (+ ~3.5 °C in soils) and cooler (-~3.5 °C in soils) locations along an altitudinal gradient in the Tibetan area. We found that fruit-set dates remained relatively stable under both warming and cooling during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 61 publications
4
38
2
Order By: Relevance
“…Eurybia macrophylla advanced fruit maturation, while Trientalis borealis showed no notable fruit maturation in +3.4°C and a trend toward delayed fruit maturation in +1.7°C compared to ambient. Our study agrees with other warming studies, which also found no change in timing of fruit maturation with warming (Farnsworth et al, 1995;Price and Waser, 1998;Jiang et al, 2016), though a response may be species specific according to our findings. The differing responses, advance, delay and no change, in fruit maturation to warming could occur for several reasons.…”
Section: Discussionsupporting
confidence: 92%
“…Eurybia macrophylla advanced fruit maturation, while Trientalis borealis showed no notable fruit maturation in +3.4°C and a trend toward delayed fruit maturation in +1.7°C compared to ambient. Our study agrees with other warming studies, which also found no change in timing of fruit maturation with warming (Farnsworth et al, 1995;Price and Waser, 1998;Jiang et al, 2016), though a response may be species specific according to our findings. The differing responses, advance, delay and no change, in fruit maturation to warming could occur for several reasons.…”
Section: Discussionsupporting
confidence: 92%
“…It seems that the durations could be lengthened, unchanged, or shortened in both study year. This is consistent with the observation that the effects of climate change on the duration of reproduction are diverse (Price and Waser, 1998;Sherry et al, 2007;Post et al, 2008;Jiang et al, 2016). The mechanisms underlying the diverse response are unknown.…”
Section: Discussionsupporting
confidence: 91%
“…The flowering stage accounted for 70% of the extension to the reproductive phase under warming and for 58% of the extension to the activity period on average across species. Advanced first flowering appears to be the main contribution to prolonged flowering duration under warming, as opposed to later last flowering4. Some experiments have found either longer flowering or maintenance of flowering duration under warmer temperatures, depending on the species17262728, whereas other experiments have found a shorter duration of flowering and other individual reproductive stages under warming62229.…”
Section: Discussionmentioning
confidence: 95%